2017
DOI: 10.14236/jhi.v24i4.949
|View full text |Cite
|
Sign up to set email alerts
|

Research Outputs of England’s Hospital Episode Statistics (HES) Database: Bibliometric Analysis

Abstract: Background Hospital administrative data, such as those provided by the Hospital Episode Statistics (HES) database in England, are increasingly being used for research and quality improvement. To date, no study has tried to quantify and examine trends in the use of HES for research purposes. Objective To examine trends in the use of HES data for research. Methods Publications generated from the use of HES data were extracted from PubMed and analysed. Publications from 1996 to 2014 were then examined further in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 7 publications
(4 reference statements)
0
16
0
Order By: Relevance
“…However, a recent systematic review of diagnostic and procedural coding accuracy identified three studies which used four-digit ICD-10 diagnostic codes and identified diagnostic data accuracy of 71.0% (Gibson & Bridgman, 1998), 95.9% (Kirkman et al, 2009) and 87% (Audit Commission, 2010) compared to an overall accuracy of 80% across the 23 studies (Burns et al, 2011). The use of HES data for research has increased despite the lack of consensus on the acceptable level of data accuracy (Chaudhry et al, 2017). Albeit that overall data accuracy in the NHS has improved since the introduction of financial reimbursements in 2004 the likely variation in data accuracy, underidentification of alcohol disorders by non-specialist clinicians (Mitchell et al, 2012) and the limitations in the identification of ED clinical diagnosis will have resulted in conservative estimates of alcohol disorders in this study.…”
Section: Discussionmentioning
confidence: 94%
“…However, a recent systematic review of diagnostic and procedural coding accuracy identified three studies which used four-digit ICD-10 diagnostic codes and identified diagnostic data accuracy of 71.0% (Gibson & Bridgman, 1998), 95.9% (Kirkman et al, 2009) and 87% (Audit Commission, 2010) compared to an overall accuracy of 80% across the 23 studies (Burns et al, 2011). The use of HES data for research has increased despite the lack of consensus on the acceptable level of data accuracy (Chaudhry et al, 2017). Albeit that overall data accuracy in the NHS has improved since the introduction of financial reimbursements in 2004 the likely variation in data accuracy, underidentification of alcohol disorders by non-specialist clinicians (Mitchell et al, 2012) and the limitations in the identification of ED clinical diagnosis will have resulted in conservative estimates of alcohol disorders in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Although generalisations from these study findings to other populations should be made with caution, previous research has shown that the study population matches the overall age-sex and chronic disease prevalence distribution of the UK well, while being more ethnically diverse. The SUS data, and the derived hospital episode statistics, are a well-established source of data for observational studies in England 24. A systematic review found that the accuracy of clinical coding used in such databases is sufficiently robust for research purposes 25.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the three databases directly promoted scientific research and researchers now are recognizing their full potential. Chaudhry et al (2017b) extracted the publications from WoS and PubMed to examine the usage trends of the Hospital Episode Statistics (HES) database in England. Annual distribution of publications and research categories of the publications were used as metrics in Chaudhry's study.…”
Section: Literature Reviewmentioning
confidence: 99%